Past climate and continentality inferred from ice wedges at Batagay megaslump in the Northern Hemisphere's most continental region, Yana Highlands, interior Yakutia - T. Opel; J. B. Murton; S. Wetterich; H. Meyer; K. Ashastina; F. Günther; H. Grotheer; G. Mollenhauer; P. P. Danilov; V. Boeskorov; G. N. Savvinov; L. Schirrmeister (Climate of the Past, 2019)
Ice wedges in the Yana Highlands of interior Yakutia – the most continental region of the Northern Hemisphere – were investigated to elucidate changes in winter climate and continentality that have taken place since the Middle Pleistocene. The Batagay megaslump exposes ice wedges and composite wedges that were sampled from three cryostratigraphic units: the lower ice complex of likely pre-Marine Isotope Stage (MIS) 6 age, the upper ice complex (Yedoma) and the upper sand unit (both MIS 3 to 2). A terrace of the nearby Adycha River provides a Late Holocene (MIS 1) ice wedge that serves as a modern reference for interpretation. The stable-isotope composition of ice wedges in the MIS 3 upper ice complex at Batagay is more depleted (mean δ18O about −35 ‰) than those from 17 other ice-wedge study sites across coastal and central Yakutia. This observation points to lower winter temperatures and therefore higher continentality in the Yana Highlands during MIS 3. Likewise, more depleted isotope values are found in Holocene wedge ice (mean δ18O about −29 ‰) compared to other sites in Yakutia. Ice-wedge isotopic signatures of the lower ice complex (mean δ18O about −33 ‰) and of the MIS 3–2 upper sand unit (mean δ18O from about −33 ‰ to −30 ‰) are less distinctive regionally. The latter unit preserves traces of fast formation in rapidly accumulating sand sheets and of post-depositional isotopic fractionation.